2019
DOI: 10.29328/journal.cjog.1001031
|View full text |Cite
|
Sign up to set email alerts
|

Gynaecological malignancies after breast cancer diagnosis: A population-based study

Abstract: Background: Breast cancer (BC) is one of the most prevalent malignancies. BC survivors have higher risk of second primary cancers than the general population. There is an increased interest in BC survivor management, including the prevention of these second cancers. The aim of this study was to assess the risk of gynaecological malignancy (GM) as second neoplasm among BC patients in our population. Methods: Patients with invasive BC diagnosed from 1980 to 2014 included in the Girona Cancer Registry were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Mortality risk was higher in the BC cohort than in the general population for endometrial and ovarian cancer, a result consistent with our previous studies of the risk of second tumours after BC diagnosis [32]. The BC patients in our cohort who died from endometrial cancer were diagnosed with BC, on average, at 70 years of age (see Supplementary Material Figure S2), older than the BC patients in our cohort who died from BC (close to 60 years of age).…”
Section: Cancer Causessupporting
confidence: 91%
See 1 more Smart Citation
“…Mortality risk was higher in the BC cohort than in the general population for endometrial and ovarian cancer, a result consistent with our previous studies of the risk of second tumours after BC diagnosis [32]. The BC patients in our cohort who died from endometrial cancer were diagnosed with BC, on average, at 70 years of age (see Supplementary Material Figure S2), older than the BC patients in our cohort who died from BC (close to 60 years of age).…”
Section: Cancer Causessupporting
confidence: 91%
“…The BC patients in our cohort who died from endometrial cancer were diagnosed with BC, on average, at 70 years of age (see Supplementary Material Figure S2), older than the BC patients in our cohort who died from BC (close to 60 years of age). Endogenous and exogenous hormones could play a role in this outcome [33], as could potential surveillance bias after the diagnosis of BC or tamoxifen treatment, which is related to the development of endometrial hyperplasia and cancer [32][33][34][35][36][37]. Regarding oestrogen receptor or progesterone status [38], common aetiological factors among BC subtypes might also increase the risk of endometrial cancer [39][40][41][42].…”
Section: Cancer Causesmentioning
confidence: 99%
“…Multiple studies have shown an increased risk of endometrial cancer in association with prolonged tamoxifen use. Some authors published an increased risk of aggressive histology of endometrial cancer with poor prognosis in those treated with tamoxifen [ 18 , 25 ] while others have not found this relationship [ 14 , 24 ].…”
Section: Discussionmentioning
confidence: 99%